Análisis bibliométrico de fuentes documentales en la Revista de Psicología de la Pontificia Universidad Católica del Perú (1983-1992) - Vargas López, Marco (1996)
Peruvian psychology is istudied through one of íts most representatíve periodical publications: The Psycholical Journal -published by Peruvian Pontifical Catholic University-,covering from 1983 to 1992 (Vols. 1-10). Using a bibliometric methodology, the journals analyzed according to the references used througt the 113 anides published here,identif)ring totality of references used, number of primaty references, presentness, rankand languages of lists of references. On rhe other hand, Peruvian references have receivedparticular treatment, allowing this the identification of national authors and sources mostfrequently quoted in the Psychology Journal.